Nuclear policy-nuclear fuels for peaceful, safer co-generation and environmentally benign applications - Mohd Fadzil, Syazwani; Qureshi, Shafi; Basu, Sekhar; Kasturirangan, K.; Kakodkar, Anil; D. Badgujar, Kushal; M. Duxit, Prakash (International Journal of Engineering and Technology, 2020)
Here, safer nuclear fuels which can sustain in the high temperature and fluence environment of the reactor core are investigated to utilize nuclear energy peacefully. At Nuclear Fuel Complex in Hyderabad, nuclear fuels are being manufactured which are best suited for high temperature and fluence environment of the reactor core even in accidental scenarios. In this paper, nuclear fuels manufactured at NFC, Hyderabad are presented. The developed nuclear fuels have higher equivalent hydraulic diameter and breeding capability to produce U^233. Nuclear fuels having higher equivalent hydraulic diameter reduce the reactor core temperature substantially. These fuels have negative temperature coefficient of reactivity. Thus, in case of an accident, the fuel temperature never exceeds the safety limit. Therefore, the thermal heat available across the secondary of a heat exchanger can be utilized for different industrial processes. This allows the development of key technologies, such as safer co-generation of electricity and Hydrogen. The Three-Stage Indian Nuclear Power Program has been explained for nuclear disarmament. The product Hydrogen gas has been utilized in many ways for different applications. Moreover, the processing of iron ore with the energy obtained from the IHX secondary side, eliminates the burning of coals and CO2 emissions into the environment. Several radioisotopes have been developed for medical applications from spent fuel.Â Â